Development of a CNC micro-lathe for bone microimplants (2011)
This paper evaluates the development of a CNC micro-lathe concept, continuing with the research in the development of machine tool prototypes by LATEMM. A micromachining center developed in 2004-2005 at Universidad de los Andes was studied, and based on the results obtained, a new prototype was proposed. The motivation behind the design and construction of this machine tool was to achieve higher precision in the machining process compared with conventional turning produced in macro machine tools. A machine, with spindle rotation speed up to 300 000 rpm was achieved, the cutting tool moves in two axes through step motors connected to worm gear reductions, thus resolution of 1μm is achieved. The interpolator was programmed based on DDA integration. The machine was set under a stereoscope to visualize the machining operations with zoom up to 30X. Micromachining was reached adopting NC control and it was possible to characterize micro-turned cortical bone samples.